Spatial distribution and risk assessment of heavy metal(loid)s in sediments and marine organisms in the Yellow River estuary and its adjacent areas, China - Wang, Enkang; Wang, Jing; Sun, Yonggen; Zhao, Jinxia; Zhang, Zhiwei; Xu, Guoqiang; Zhang, Yongqiang; Zhang, Daolai (Frontiers in Marine Science, 2025)
IntroductionHeavy metal(loid)s (HMs) are widespread pollutants in marine ecosystems that are disseminated through natural and anthropogenic activities.MethodsTo ascertain the extent of HM in the Yellow River estuary and its adjacent areas, the contents of seven HMs were determined in 103 surface sediments and 82 marine organisms collected in October 2022. The pollution status and potential ecological risks were analyzed and evaluated using various indicators.ResultsThe results showed that, apart from Hg, all other HMS in the surface sediments had similar spatial distributions and were mainly derived from natural sources. Hg had an anthropogenic source and showed a very high potential ecological risk in the old Yellow River estuary. The average HM concentrations in marine organisms were in the order of Zn > Cu > As > Cr > Cd > Pb > Hg. Except for As and Cu in fish—which exceeded the standard at some stations—all other standard indices met the corresponding biological quality standards. The target hazard coefficients for the seven HMs were in the order of Cu > Cd > As > Zn > Cr > Hg > Pb. The target hazard coefficient of a single HM in all marine biological samples was <1, indicating that a single HM had no significant negative effects. The BSAF values of Cd and Hg in crustaceans, and Cu, Cd, and Hg in mollusks and fish were all >1, suggesting that these three organism types accumulated Cu, Cd, and Hg from surface sediments.ConclusionThe findings of this study can serve as a theoretical foundation for the prevention and control of HM pollution in the Yellow River Basin.